Uma análise dos determinantes da participação dos trabalhadores cearenses no mercado informal - Cavalcante, Sandra Régia Costa (2010)
The aim of this study to estimate the probability of a worker being employed in the informal sector conditioned their productive characteristics, considering the possibility of sample selection bias. The sample is restricted to Ceará, and uses the National Survey of Household Sample Survey (PNAD) in 2008 to classify workers in formal and informal. According to the dual hypothesis, the jobs in the formal sector are indeed better in many dimensions, and the existence of informality is because the number of these jobs is limited. If indeed there is segmentation in the labor market and rationing of formal jobs, it is important to know how the allocation of workers between the two sectors. For this is considered the possibility of selection bias in the choice between formal and informal sectors. The selection bias occurs when a number of unobservable characteristics of individuals can make them end up working, by choice or necessity, in the informal economy. That is, unobservable characteristics of individuals such as skill, willpower, determination, creativity etc., it may be influencing the choice between working in the formal or informal.